Numerical modeling of the fire behavior of reinforced concrete tunnel slabs during heating and cooling. (1st May 2022) - Hua, Nan; Elhami Khorasani, Negar; Tessari, Anthony
Highlights: The fire behavior of reinforced concrete tunnel slabs during both the heating and cooling phases are simulated. Three modeling strategies are investigated using beam, shell, and solid elements. Five recent fire tests on loaded and restrained large-scale tunnel slabs, with varying concrete strengths, restraint levels, and fire scenarios, are selected to verify the models. Temperature and displacement evolutions during heating and cooling obtained from the numerical models are compared with the experimental test data. Shell elements perform the best by achieving a balance between model accuracy and efficiency. Abstract: This paper examines different modeling approaches to simulate the behavior of reinforced concrete (RC) tunnel slabs under fire during both the heating and cooling phases. Three modeling strategies are investigated by using beam, shell, and solid elements in addition to different methods to capture the effect of axial restraint on the slabs. The models consider temperature-induced plastic deformations and irrecoverable degradation of materials. The models also utilize distinct concrete properties for heating and cooling as well as account for the transient creep strain explicitly in the calculations. The results obtained from different modeling strategies are compared to five recent fire tests on loaded and restrained large-scale RC tunnel slabs, with varying concrete strengths, restraint levels, and fire scenarios. Temperature and displacement evolutions during heating and cooling obtained from the numerical models are compared with the experimental test data. When considering model accuracy and efficiency as the primary performance metrics, using shell elements to analyze the fire performance of reinforced concrete tunnel segments resulted in the best balance between the two. The numerical models and techniques developed in this paper will enable practicing engineers to reliably and rapidly assess fire damage to reinforced concrete tunnel linings, and to explore cost-effective designs of tunnels for fire.